Molecular analysis of dog and wolf genomic DNA to explore integration polymorphisms of Canine Endogenous Retroviruses, CfERV - Mirzazadeh, MohammadReza (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
Endogenous retroviruses (ERVs) are found in all examined vertebrate genomes. Different mammals have been reported to contain different amounts of ERVs. For example, in the dog genome 0.15% of sequences are derived from retroviruses. Genome rearrangements driven by retroviral transposition likely have had effects on plasticity of mammalian genomes. During evolution, occasionally, exogenous retrovirus (XRVs) infected germ line cells and the acquired provirus might have been transmitted vertically from generation to generation as a normal Mendelian trait. These rare events of germline infections will result in the generation of ERVs. To gain further insights into the nature of Canine Endogenous Retroviruses (CfERVs) we have performed a PCR-based survey of insertional polymorphism of those CfERVs that were estimated to have integrated recently due to the low degree of divergence of their respective 5’ and 3’ long terminal repeats (LTRs). The presence of potential integration polymorphism was analysed in genomic DNA prepared from different dog breeds and several wolves by using locus-specific primers for CfERV-chromosomal junctions. We did not find any evidence for integration polymorphism for the CfERV-Fc4 group, which may indicate that integration of this group of CfERVs occurred prior to domestication of dogs from Canis lupus. Furthermore, using sequence annotation tools the implication of CfERVs in canine copy-number variation (CNVs) was estimated and we have found evidences for overlap between CfERVs and CNVs.